α-TubK40me3 is required for neuronal polarization and migration by promoting microtubule formation - Xuan Xie; Shaogang Wang; Mingyi Li; Lei Diao; Xingyu Pan; Jijun Chen; Weiguo Zou; Xu Zhang; Wenfeng Feng; Lan Bao (Nature Communications, 2021)
Post-translational modifications of tubulins regulate microtubule properties and neural development. Here, the authors report that one such post-translational modification, α-TubK40me3, is required for neuronal polarization and migration by promoting microtubule formation.